Epilepsy in de Vivo syndrome: a literature review and a clinical case - M. B. Mironov; N. I. Andreeva; D. S. Fomchenkova; N. V. Chebanenko; Yu. V. Rubleva; T. M. Krasilshchikova; S. G. Burd (Эпилепсия и пароксизмальные состояния, 2019)
GLUT 1 transporter deficiency syndrome (De Vivo syndrome, GLUT 1 deficiency syndrome, De Vivo Disease) is a rare genetic disease associated with a deficiency of the glucose transporter GLUT 1. Due to this deficiency, diffusion of glucose through the blood-brain barrier is limited or completely blocked. As a result, a clinical symptom complex of neurological disorders – epileptic seizures, cognitive deficit, and motor disorders – develops. The article provides a review of the literature on the variety of epilepsy manifestations in this syndrome, including idiopathic generalized epilepsy with absences, myoclonic-astatic epilepsy, and focal epilepsy. The inability of the basic antiepileptic therapy to stop the seizures is noted. The main treatment method is the ketogenic diet. A clinical observation made by these authors is also presented.